Factors Affecting Employee Engagement and Its Relation to Employee Performance - Achmad Rizky Nevianto; Dedi Heriyanto; Mur Adi Setijoutomo; Anita Maharani (Journal of Research in Business, Economics, and Education, 2021)
Employee engagement is viewed as a mediator between work spirituality, reward, and punishment on employee performance in this study. The researcher used theories linked to the variables investigated in this study for the literature review. The researcher uses a structural model technique to help interpret the data gathered by distributing questionnaires to Indonesian mining businesses as a research method. The findings show that there are a variety of proved and unproven ideas, which reflects an intriguing occurrence in mining companies: employee performance is not driven by employee engagement, but rather by punishment and work spirituality.